2022
DOI: 10.3390/su14063522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Planning on Elderly Individual Quality of Life in Severe Cold Regions: A Case Study in Northeastern China

Abstract: With the development of urbanization and the ageing population, the improvement of the urban environment and the quality of life (QOL) of the elderly in cities with a cold climate have become critical issues to be addressed. However, only a few studies have focused on this aspect. According to a review of the literature, the contents of the built environment (BE) in severe cold regions are defined as thirteen key factors of four categories (density, environmental aesthetics, outdoor environment, and accessibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…An essential characteristic of a winter city is the climate, especially in winter. There are five specific characteristics of cold urban winters, including temperatures generally below 0°C, precipitation often in the form of snow, short daylight and sunshine hours, long duration of the above three characteristics, and distinct seasonal changes (Leng, 2009). As a stable and persistent natural factor, the cold climate significantly impacts the built environment, urban energy consumption, the inhabitants themselves, and the socio-economic development of cities.…”
Section: Content Of Urban Research On Chinese Winter Citiesmentioning
confidence: 99%
See 2 more Smart Citations
“…An essential characteristic of a winter city is the climate, especially in winter. There are five specific characteristics of cold urban winters, including temperatures generally below 0°C, precipitation often in the form of snow, short daylight and sunshine hours, long duration of the above three characteristics, and distinct seasonal changes (Leng, 2009). As a stable and persistent natural factor, the cold climate significantly impacts the built environment, urban energy consumption, the inhabitants themselves, and the socio-economic development of cities.…”
Section: Content Of Urban Research On Chinese Winter Citiesmentioning
confidence: 99%
“…The third stage is the rapid development stage. The publication of scholar Leng Hong's book "Study on Urban Environmental Livability in Cold Regions" has led to a surge of research on livable cities in the academic community of winter cities in China (Leng, 2009). The volume of literature on related studies has entered an explosive period.…”
Section: Progress Of Urban Research On Chinese Winter Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However there have been limited studies evaluating recreation areas, especially in areas where winter conditions are quite severe, such as Erzurum (Gao et. al., 2018;Leng and Han, 2022;Ogawa et. al., 2019;Wang et.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that older adults who live near parks and have good interaction with parks have better psychological well-being [12]. Additionally, park environments can improve energy levels, restore attention, alleviate stress, improve mood, and enhance happiness through the provision of good spatial elements and spaces with different attributes [13][14][15][16]. At present, relevant research focuses on exploring the correlation between park characteristics and the health recovery effects of specific populations.…”
Section: Introductionmentioning
confidence: 99%